2003
DOI: 10.1046/j.1440-169x.2003.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans DAF‐21 (HSP90) is characteristically and predominantly expressed in germline cells: Spatial and temporal analysis

Abstract: Three monoclonal antibodies against antigens that exist in the Caenorhabditis elegans germ line have previously been described. In the present study, a full-length mRNA for one of these antigens was isolated, and by sequencing its corresponding cDNA, it was predicted that the protein would show a high homology with the 90 kDa heat shock protein (HSP90) in other species, and with the protein of daf-21 , a previously identified hsp90 homologue. The spatial and temporal distribution of the antigen (DAF-21) was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…In C. elegans, all eggs are equally competent to hatch without any external stimulation (Albert and Riddle, 1988). The sensitivity of C. elegans egg hatch to GA exposure suggests the involvement of Hsp90 in this process, which is consistent with evidence for the presence of Hsp90/DAF-21 within the germline (Inoue et al, 2003). In contrast to C. elegans, the hatching process in cyst nematodes is complex, asynchronous, and influenced by environmental and host-derived factors (reviewed in Perry, 1997).…”
Section: Discussionsupporting
confidence: 75%
“…In C. elegans, all eggs are equally competent to hatch without any external stimulation (Albert and Riddle, 1988). The sensitivity of C. elegans egg hatch to GA exposure suggests the involvement of Hsp90 in this process, which is consistent with evidence for the presence of Hsp90/DAF-21 within the germline (Inoue et al, 2003). In contrast to C. elegans, the hatching process in cyst nematodes is complex, asynchronous, and influenced by environmental and host-derived factors (reviewed in Perry, 1997).…”
Section: Discussionsupporting
confidence: 75%
“…However, the apparent integrity of the pole plasm in Hsp83 stc /Hsp83 E317K ovaries and embryos (Figures 6 and 7) and the rescue of pgc localization upon overexpression of a single kinase (Figure 8) are consistent with the idea that the defects in pgc (and perhaps also nos) localization arise from the reduction in activity of a few discrete Hsp90 clients. Hsp83 mRNA is itself concentrated in the pole plasm (Ding et al 1993) and Hsp90 is found at particularly high levels in the germ line precursors of other organisms (Vanmuylder et al 2002;Inoue et al 2003), which may reflect a conserved role in mRNA localization.…”
Section: Discussionmentioning
confidence: 96%
“…Before use, the EOR-1 antibody was preabsorbed with acetone powder made from eor-1(cs28) animals and diluted 1:2000. The anti-HSP90 antibody, a gift from Johji Miwa and Yasunori Yamaguchi, was previously described (Inoue et al 2003) and used at 1:1,000 to control for loading. The MEL-26 antibody, a gift from Paul Mains, was previously described (Pintard et al 2003) and used at 1:500.…”
Section: Methodsmentioning
confidence: 99%